PEMALSUAN SURAT KETERANGAN HASIL TES COVID-19 OLEH DOKTER DIPANDANG DARI HUKUM PIDANA DAN KODE ETIK KEDOKTERAN - Maya Anissa Yambo; Nugroho Adipradana (Gloria Justitia, 2021)
The Covid-19 global pandemic has been around for almost two years. One of the most prominent legal problems related to the pandemic is the forgery of Covid-19 test result certificates. A certificate indicating that a person is tested negative for Covid-19 is essential for many occasions, for instance, traveling. Doctors and health workers are the parties that are heavily involved in the process of testing and issuing the result, thus giving them an opportunity to commit such crime. In this article, there will be an explanation regarding the regulations and sanctions based on Indonesian criminal law and KODEKI (Indonesian Medical Code of Ethics) for doctors who commit the crime of counterfeiting Covid-19 test result certificates. The research is conducted using normative research methods where secondary data is the main resource. From this research, we can conclude that the regulations and criminal sanctions for the crime mentioned above can be found in Article 267 of the Criminal Code and Article 93 of the Health Quarantine Law. Meanwhile, based on KODEKI, a doctor who counterfeited Covid-19 results is violating Article 1, 7, and 12 KODEKI. Such Actions are classified as both ethical and legal violation.